Social network size estimation and determinants in tehran province residents. - Mohsen Shati; AliAkbar Haghdoost; Reza Majdzadeh; Kazem Mohammad; SeyedeSalehe Mortazavi (Tehran University of Medical Sciences, 2014)
Network scale-up is an indirect method for estimating the size of hidden, hard-to-count or high risk populations. Social network size estimation is the first step in this method. The present study was conducted with the purpose of estimating the social network size of the Tehran Province residents and its determinants.Maximum Likelihood Estimation was applied to estimate people's network sizes by using populations of known sizes and the scale-up method. Respondents were selected from Tehran province through convenience sampling in 2012. Out of thirteen selected subpopulations with known size, ten had minimum accuracy which used in our analysis.Of the 1029 respondents in this study, 46.7% were male. The social network size of Tehran Province residents was estimated to be 259.1 (CI95%: 242.2, 276) based on the ten known populations remained in this study. This size was 291.8 in men and 230.4 in women. Younger people (18-25 years old) had larger network sizes compared to the other age groups (P